The nature of the Patrilineal System of Bali Indigenous Communities towards the legal position of women in instruction - Cokorda Gede Swetasoma; Moch. Isnaeni; Endang Prasetyawati (Technium Social Sciences Journal, 2021)
This research is a normative juridical research by looking at the provisions in Balinese customary inheritance law. The essence of the patrilineal system of the Balinese indigenous people to the legal position of women is to place women in an inferior position. This condition has an impact on the position of women which causes gender inequality. Traditional inheritance in Bali is based on swadharma (obligations) and swadikara (rights). Men are placed as heirs because they have responsibilities both to their ancestors, parents, and in traditional communities. In its development, married daughters actually take over the responsibility for praying at the home of the family of origin and taking care of their parents, even holding a funeral ceremony for their parents, while boys live separately from their parents. The condition in which girls aren’t entitled to inherit the assets of their parents is certainly unfair.